Will you be my valenswine? - Bateman, Teresa; Stephenson, Kristina (Morton Grove, Ill. : Albert Whitman, 2005)
A sad piglet named Polly searches the pasture, forest, and barnyard for someone to love her, only to discover that her valenswine has been there all along.
"An Albert Whitman Prairie Paperback" -- Cover p. [4]
Keywords: Valentines; Swine; Mother and child